Removal Of Tetracycline Hydrochloride Antibiotic From Water Using An Ozonation Alone And Combination Of Ozonation And Sonolysis - Jayaprakas, Sharvin (Universiti Sains Malaysia, 2021)
Tetracyclines (TCs) are a class of diverse antibiotics that have a wide range of applications in human, veterinary, and aquaculture treatment. TCs residues are ubiquitous in soil, surface water, groundwater, and even drinking water due to the ongoing release of TCs residues into the environment and insufficient removal through conventional treatment systems. The establishment of TCs resistance in a wide range of bacteria demonstrates the severity of the TCs pollution. The degradation of TC antibiotic using ozonation alone and a combination of ozonation and sonolysis is discussed in this publication. Concentration, pH, and catalyst weight are three criteria that have been studied to determine the optimal antibiotic degradation efficiency. The ozone output supply was constant throughout the experiment. For an initial concentration of antibiotic, the results obtained shown that gnvhh can degrade TC antibiotic faster at a very low concentration, 30 ppm and the degradation efficiency was 85.96% within 5 minutes of the reaction. The results shown that for higher concentration, the reaction time needed increases. At an initial pH of 9, the degradation of antibiotic showed higher percentage of degradation efficiency. More than 79% of antibiotic was degraded after 5 minutes of the reaction. For highest weight of catalyst, which is 0.25 g, the degradation efficiency of TC antibiotic achieved 84.75 % also within 5 minutes of reaction. Kinetic analysis showed that the ozonation of the TC antibiotic represented the first order reaction. The results reaction of ozone together with sonolysis was more effective compared to ozone alone. The degradation efficiency of TC antibiotic at concentration of 60 ppm at 5 minutes of reaction was 92.1% with sonolysis and 89.8% for ozone alone. The synergy observed in the combined schemes, mainly due to the effects of ultrasound in enhancing the O3 decomposition, led to a higher mineralization for 2 hours treatment and to a significantly higher mineralization level for shorter treatment duration. The results obtained before and after sonolysis and ozonation applied jointly found to be a promising technology for TC degradation in wastewater solution. This is attributed to the enhanced O3 are degradation by collapsing bubbles that may yield additional free radicals. The study's findings were examined, and some future research in antibiotic degradation was suggested for more effective approaches.